Nutritional and bioactive constituents of antioxidant and antimicrobial properties in Spinacia oleracea: a review - Nur Huda-Faujan,; Saiful Irwan Zubairi,; Auni Afiqah Ahmad Baker, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In recent years, overwhelming studies have recognized the excellent functional and nutritional properties of green leafy vegetables that can be gained through a proper human diet. Among the vegetables studied, Spinacia oleracea Linn. or commonly known as spinach is widely being acknowledged for having a diverse range of nutritional composition and bioactive phytochemical compounds. Spinach, which is grouped under the Amaranthaceae family, contains various beneficial effects owing to their nutritional compositions, such as carbohydrates, proteins, fats, fibre, minerals, vitamins, and bioactive constituents that are directly linked to various bio-functional properties. The valuable bio-constituent of polyphenols that exist in spinach contributes to its effective antioxidant and antimicrobial properties. Therefore, the antioxidant from spinach extract is a promising source of natural antioxidants to replace the harmful effect of synthetic antioxidants. Moreover, it can inhibit cellular oxidative damage, increase storage stability, and restrict the growth of a wide range of pathogenic bacteria, which offers a huge prospect for potential food application. The main attention of this review was to highlight the effective antioxidant and antimicrobial properties of phytochemical compounds in spinach extract. Additionally, this review provided a comprehensive description of the wide range of food applications with regards to the use of spinach extract.